Exploring Professionalism and Ethical Challenges of Artificial Intelligence in Journalism - Noor-Ul-Hayee; Nizamani, Farheen Qasim; Nizamani, Muhammad Qasim; Chandio, Dastar Ali (ACADEMIA International Journal for Social Sciences, 2026)
The study’s objectives are to understand the evolution of the idea of artificial intelligence in journalism, develop a scientific definition for it in light of the variety of terms and concepts, define the function of algorithms in journalistic editing, and pinpoint the benefits of AI journalism, its superiority over traditional journalism, as well as the main ethical, professional, and technical issues it faces. The analytical descriptive method of researching foreign literature that looks at how journalism is affected by AI technology. The study came to the following conclusions: creating a thorough definition of the term "artificial intelligence journalism," demonstrating how AI has improved newsroom productivity, increased the amount and variety of content produced, as well as boosting media organizations’ financial returns, and that semantic limits continue to be a problem for artificial intelligence journalism Therefore, the central problem of this study is to examine how journalism education can effectively adapt to the rise of AI while addressing its professional, ethical, and technological challenges. Specifically, this study seeks to explore the extent to which AI is influencing journalistic professionalism, identify key ethical concerns associated with its use, and assess the preparedness of media students to operate responsibly in an increasingly automated news environment. Artificial Intelligence has transformed journalism by improving efficiency and content production capacity, it simultaneously challenges core journalistic values such as accuracy, transparency, and accountability. The lack of human editorial judgment in AI systems increases the risk of misinformation and ethical ambiguity. Therefore, a balanced integration of AI in journalism is necessary, supported by strong ethical frameworks, transparency mechanisms, and professional oversight to ensure credibility and public trust in media systems